Pulsar test of a violation of discrete symmetries in gravitation - Losecco, J. M.; Matsas, G. E A [UNESP]; Natale, A. A. [UNESP]; Pacheco, J. A F (Elsevier, 1989)
We determine an improved limit on C and P violation to the extended gravitational potential of Leitner and Okubo using the millisecond pulsar PSR 1937+214 data. © 1989.